Radio Komunitas Merapi FM Studi Tentang Keterlibatan Komunitas dalam Pengelolaan Radio Merapi FM - Priyandono W. Atmojo, Edi Panutra & (Transformasi, 2012)
AbstractThe advent of â€œUU 32 Tahun 2002â€ in Indonesia that legalized the existence of the radiocommunity cannot automatically solve the problem of the existence the radio community. Theradio community was founded by the community, organized by the community to serve the realinterests of the community often cannot properly established. Qualitative research withinteractive analysis revealed the presence of Radio Merapi FM as a radio community located onthe slopes of Mount Merapi. Radio Merapi FM initially founded as a hobby and developed intoradio community, although it has been arranged in accordance with the rules of organization ofradio community, but in the practice has not been well established due to time management andthe ability of community, also because of the limited funds.Key Words : Community Radio, Management, Limited Funds